2021
DOI: 10.1155/2021/3499645
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Mechanical and Water Absorption Behaviour of Basalt Fiber Reinforced Polymer Matrix Composites with Different Epoxies as Matrix for Biomedical Applications

Abstract: In comparison to conventional materials, polymer matrix composite materials have witnessed a surge in applicability due to their higher specific strength-to-weight ratio, abundant availability, and ease of shaping. Due to technological, economic, environmental, and societal challenges, bio-based fibers began to emerge quickly for use in industrial components. Due to its unique chemistry-related characteristics, basalt fiber holds a prominent position among the many bio-based fibers. So, it could be thought of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This method is quite attractive for its low cost [121]. For instance, Rao et al prepared woven basalt fiber (55% fiber load) reinforced with Araldite LY556-Araudr HY951 prepared by hand layup and showed that this composite had excellent water absorption behavior and mechanical strengths, which could be used in biomedical applications [122].…”
Section: Hand Layupmentioning
confidence: 99%
“…This method is quite attractive for its low cost [121]. For instance, Rao et al prepared woven basalt fiber (55% fiber load) reinforced with Araldite LY556-Araudr HY951 prepared by hand layup and showed that this composite had excellent water absorption behavior and mechanical strengths, which could be used in biomedical applications [122].…”
Section: Hand Layupmentioning
confidence: 99%
“…Some research has been conducted utilizing natural fibers as reinforcement materials embedded in an epoxy matrix for biomedical applications. For instance, in order to develop a matrix for biomedical applications, Rao et al [10] conducted a comparative analysis of the mechanical and water absorption behaviour of basalt fibre reinforced polymer matrix composites with various epoxies. In this study, an examination was conducted wherein plain-woven basalt fiber was utilized as a reinforcement material at a constant percentage of 55% in conjunction with three distinct epoxy resin-hardener combinations as a matrix.…”
Section: Introductionmentioning
confidence: 99%